Suppression of basal stem rot disease progress in oil palm (elaeis guineensis) after copper and calcium supplementation - Ahmad Azmi, Nur Sabrina; Meon, Sariah; Abdul Rahman, Zaharah (Universiti Putra Malaysia Press, 2012)
The effects of copper and calcium nutrient supplementation on basal stem rot disease caused by Ganoderma boninense were evaluated in oil palm during a 6-month glasshouse study. Nutrients were supplemented when seedlings were at the 2- to 3-leaf stage. The aim of the study was to assess the effects of copper and calcium on the suppression of basal stem rot. Nutrient supplementation, with copper at 2.0 mg/L and calcium at 4000 mg/L alone or in combination, significantly reduced G. boninense infection in oil palm roots. The treated seedlings did not escape the disease, but it developed more gradually than in the untreated seedlings. The seedlings supplemented with a combination of calcium and copper remained free from any symptom for a longer period and developed the disease at a later stage than the controls. The supplementations of calcium and copper could have triggered oil palm mechanism of resistance by enhancing the production of peroxidase and lignin during fungal penetration. These findings suggested that copper and calcium supplementations could be used to reduce the severity of basal stem rot in oil palm.